Investigation of the Conceptual Knowledge of Preschool Teacher Candidates on Science Education - DAĞDELEN, Ece Nur; ATASOY, Volkan (Kastamonu Egitim Dergisi, 2023)
Purpose: This study aims to investigate the conceptual knowledge of preschool teacher candidates toward science education. Design/Methodology/Approach: Thirty-eight junior teacher candidates at a state university in the Black Sea Region of Turkey participated in the research. The study is a qualitative type of research, and Interviews and activity plans were used for data collection. The content analysis method was applied in the analysis of the data. After the responses of the teacher candidates were noted, they were coded and divided into categories. Then, themes were created according to these categories and the findings were interpreted under these theme headings. Findings: The research findings revealed that preschool teacher candidates lack adequate conceptual knowledge toward science education, especially in using science process skills, determining the role of preschool teacher in science education. Highlights: The education given in preschool teacher education undergraduate programs should not remain only at the theoretical level, teacher candidates should be allowed to practice in the preschool science education course, and it is believed that each teacher should be given information about current and different methods to use in their professional lives, and encouraged to use them in their teaching profession.
Keywords: Eğitim Üzerine Çalışmalar; Studies on Education; Preschool; Teacher candidates; Science education; Conceptual knowledge; Qualitative research; 4. Education